Clinical and genealogical assessment of patients with incontinentia pigmenti in the Ural region (Russia) between 1976 and 2012. - Toropova, N.P.; Sorokina, К.N.; Rimar, О.G. (European Journal of Pediatric Dermatology, 2012)
This paper presents the results of the follow up of 33 patients diagnosed with incontinentia pigmenti between 1976 and 2012. Cutaneous manifestations of the disease were diagnosed in 12 girls within the first year of life, including 4 in the neonatal period, and three boys. Three family trees in 4 generations are presented, including 14 female patients having various manifestations of the disease affecting the skin, teeth, eyes, etc. The prognosis depends in part on the extracutaneous associated malformations, which may range from minor to severe.